2011
DOI: 10.1007/s11483-011-9216-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soy Soluble Polysaccharide on the Stability of Soy-Stabilised Emulsions During In Vitro Protein Digestion

Abstract: This study investigated physicochemical properties of soy soluble polysaccharide (SSP) and pectinase-hydrolysed soy soluble polysaccharide (PH-SSP) from okara, the residue from soy milk production, and their influences when used as a fibre source in oil-in-water (o/w) emulsions. Although pectinase hydrolysed only the carbohydrate fraction in SSP, it resulted in the self-association of PH-SSP to the large-size aggregates. When PH-SSP was added to liquid emulsion containing 3.33% (w/v) rice bran oil and 3.75% (w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 23 publications
0
11
1
Order By: Relevance
“…The higher viscous system at high concentration of SSPS may also retard mobility of digestive enzyme, and consequently, the rate of lipid digestion was less than low viscous system. The SSPS may bind bile acid and interact with lipase, thereby reducing enzyme activity (Fafaungwithayakul et al., ). Hence, reduction in lipid digestibility of SSPS‐stabilized emulsions might be depended on various factors, such as surface ability of SSPS on oil droplet surface and viscosity of system.…”
Section: Resultsmentioning
confidence: 99%
“…The higher viscous system at high concentration of SSPS may also retard mobility of digestive enzyme, and consequently, the rate of lipid digestion was less than low viscous system. The SSPS may bind bile acid and interact with lipase, thereby reducing enzyme activity (Fafaungwithayakul et al., ). Hence, reduction in lipid digestibility of SSPS‐stabilized emulsions might be depended on various factors, such as surface ability of SSPS on oil droplet surface and viscosity of system.…”
Section: Resultsmentioning
confidence: 99%
“…They attributed this to differences in side chain composition, with the pectin containing charged sidechains and SSPS containing mostly neutral sidechains. Fafaungwithayakul, Hongsprabhas, and Hongsprabhas (2011) found that pectinase hydrolysis of SSPS could alter soy protein-based emulsion stability and proposed this as a novel means of modifying oil release, emulsion stability and proteinepolysaccharide coacervation during digestion.…”
Section: Introductionmentioning
confidence: 99%
“…The results suggest that SSPMRP-stabilized emulsions might help to increase the citral amount in the intestine with its release in a controlled manner. These results are supported by Yang et al (2015) and Fafaungwithayakul et al (2011). Negatively charged SSP might attach to the positively charged SPI molecules via electrostatic attraction, thus providing the extra stabilizing effect.…”
Section: Emulsifying Capacity Of Conjugated Spi Ssp and Sspmrp In Thmentioning
confidence: 65%
“…At pH 7.0, heat treatment (80°C, 30 min) of SPI during emulsification might reduce the insoluble conservation formation between protein and PHSSP. This might be due to the unfolding of proteins and the exposure of hydrophobic and charged reactive groups of proteins for inhibition of aggregation (Fafaungwithayakul et al, 2011). At pH 7.0, emulsion stabilized by H-SPI with 2.0% PHSSP exhibited a slight increase of protein (0.57 to 0.13%) in the sediment phase, although most of the proteins were in the emulsion phase.…”
Section: Emulsifying Capacity Of Ssp In the Peptic And Tryptic Digestmentioning
confidence: 99%
See 1 more Smart Citation